2021
DOI: 10.2478/jvetres-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cephenemyia stimulator larvae in male roe deer (Capreolus capreolus L.) in the Lublin Upland, Poland, and their impact on particular animal health indicators

Abstract: Introduction The aim of the study was to carry out epizootic assessment of male roe deer to detect the presence of Cephenemyia stimulator larvae and determine the influence of the parasite on the carcass and antler weight in animals living in different habitats. Material and Methods The investigations were based on post-mortem analysis of Cephenemyia stimulator infestations of the nasal passages and throat of 177 male roe dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…of 10% in 2015(Alagić et al 2015).Our study is the rst comprehensive study of endoparasites in wild ruminants in FBiH. The results of a study carried out in Portugal showed that almost half of the investigated deer were infested with at least one parasite, while reports from several European countries, such as those in Croatia(Kusak et al 2012), Spain(Vázquez et al 2010), the Czech Republic(Vetýška 1980) and Poland(Flis et al 2021), show a high prevalence of parasitic infestations. In Slovenia, it was determined that cause of death in 48% of necropsied animals was parasitic infestation (Žele Vengušt et al 2021).…”
mentioning
confidence: 60%
“…of 10% in 2015(Alagić et al 2015).Our study is the rst comprehensive study of endoparasites in wild ruminants in FBiH. The results of a study carried out in Portugal showed that almost half of the investigated deer were infested with at least one parasite, while reports from several European countries, such as those in Croatia(Kusak et al 2012), Spain(Vázquez et al 2010), the Czech Republic(Vetýška 1980) and Poland(Flis et al 2021), show a high prevalence of parasitic infestations. In Slovenia, it was determined that cause of death in 48% of necropsied animals was parasitic infestation (Žele Vengušt et al 2021).…”
mentioning
confidence: 60%
“…The infesta�on results in a clinical picture of behavioral altera�ons, deteriora�on of body condi�on and antler development, respiratory symptoms, loss of the ability to flee from predators, and a higher predisposi�on to other concomitant diseases. This specific parasitosis in European roe deer was first described in 1970 in Poland, and it quickly spread to other regions; currently, it is known to affect at least 12 countries (Kusak et al, 2012;Žele Vengušt et al, 2021;Flis et al, 2021). The distribu�on of Cephenemyia stimulator is widespread and exclusive across Europe, notably overlapping with the range of the roe deer.…”
Section: Introductionmentioning
confidence: 95%
“…This specific parasitosis in European roe deer was first described in 1970 in Poland, and it quickly spread to other regions; currently, it is known to affect at least 12 countries (Kusak et al, 2012; Žele Vengušt et al, 2021; Flis et al, 2021). The distribution of Cephenemyia stimulator is widespread and exclusive across Europe, notably overlapping with the range of the roe deer.…”
Section: Introductionmentioning
confidence: 99%
“…This specific parasitosis in European roe deer was first described in 1970 in Poland, and it quickly spread to other regions; currently, it is known to affect at least 12 countries [7][8][9]. However, considering it may have been understudied at that time, other potential origins for the parasitosis cannot be ruled out.…”
Section: Introductionmentioning
confidence: 99%